Tantangan Sistem Pemidanaan terhadap Anak Sebagai Pelaku Tindak Pidana dalam Sistem Peradilan Anak di Indonesia - Ketut Anjaya Wilansa Wisna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The current penal system in Indonesia focuses solely on the punitive nature of sentencing, without considering how to effectively reform the child offender for the better. This research employs a normative juridical method. The litigation process or juvenile justice system has been specifically regulated under Law Number 12 of 2011, which prioritizes the diversion system. In the litigation process, children's rights to grow, develop, and receive education must not be diminished. The educational penal system for children as criminal offenders has been regulated in Law Number 3 of 1997, particularly concerning the sanctions imposed on children as stipulated in Article 24 paragraph (1), which include: returning the child to their parents, guardian, or foster parent; handing over the child to the state to undergo education, coaching, and job training; or handing the child over to the Ministry of Social Affairs or social organizations engaged in education, coaching, and job training. The diversion system implemented in Indonesia differs from the diversion systems applied in other countries, where the system often collaborates with the Ministry of Social Affairs. According to Law Number 12 of 2011, diversion must be prioritized for children in order to prevent psychological harm. Obstacles in implementing educational sentencing or diversion systems for children arise when judges in Indonesia impose sentences rigidly based solely on statutory provisions, without considering the background, the best interests of the child, or the psychological impact of the decision, and without prioritizing justice for the child.